Efektivitas Program Sekolah Sungai dalam Meningkatkan Kesadaran Lingkungan dan Perilaku Konservasi pada Siswa Sekolah Dasar - Ahmad, Salsabila; Nathania Candra Fadillah; Wirna Amalia; Sefira Dewi Nazarina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The increasingly complex environmental damage demands preventive efforts through environmental education from an early age. This study aims to analyze the effectiveness of the Sekolah Sungai Program in increasing environmental awareness and conservation behavior in elementary school students. The research method uses a qualitative approach derived from the literature of scientific articles with related research, as well as question and answer sessions given to students regarding environmental issues and Sekolah Sungai. The results showed that the Sekolah Sungai program has succeeded in increasing public awareness, especially the younger generation, of the importance of preserving river ecosystems. Through various educational and training activities, this program not only changes people's behavior to be more environmentally aware, but also builds a strong network of cooperation between various parties. Overall, the Sekolah Sungai Program has great potential to be a solution to environmental problems, especially related to river sustainability, as well as providing wider benefits for the community and the environment, and has proven effective in increasing students' understanding of river ecosystems, the impact of environmental damage, and encouraging active participation in environmental conservation efforts